Directions of the territory’s investment security mechanisms improvement in the context of digital transformation: Krasnodar Krai case study - K. O. Ternavshchenko; V. V. Aseeva (Вестник университета)
The purpose of the study is to develop measures to improve the mechanisms for ensuring investment security of the Krasnodar Krai in the context of digital transformation.   The subject of the study is the investment and innovation potential in the economic security system of the Krasnodar Krai.   The article discusses the features of the formation of investment security of the territory in the conditions of digital transformation. The key stages of this process are presented. The analysis of innovative activity of the territory indicators formation is carried out, and the E-Government Development Index by country in 2020 is estimated. Such threats to the formation of investment security in the Krasnodar Krai as low innovative activity, fragile relationship between science and production, poor commercialization of investments; insufficient popularization of receiving state and municipal services in electronic form; unsatisfactory volume of introduction of modern end-to-end digital technologies in the field of regional management; underdevelopment of digitalisation; as well as geopolitical risks have been identified. The economic justification of the proposed measures implementation in relation to the state program “Development of the industry of the Krasnodar Territory and increasing its competitiveness”, the Strategy of digital transformation of the Krasnodar Krai, as well as the state program “Digital Economy of the Russian Federation” has been carried out. The practical implementation of the proposed measures will improve the formation of investment security of the Krasnodar Krai in the context of digital transformation.